2020
DOI: 10.1371/journal.pone.0239580
|View full text |Cite
|
Sign up to set email alerts
|

The role of health education on cervical cancer screening uptake at selected health centers in Addis Ababa

Abstract: Introduction Cervical cancer is one of the most common causes of morbidity and mortality among women in developing countries including Ethiopia. Unlike other types of cancers, the grave outcomes of cervical cancer could be prevented if detected at its early stage. However, in Ethiopia, awareness about the disease and the availability of screening and treatment services is limited. This study aims to determine the role of health education on cervical cancer screening uptake in selected health facilities in Addi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
12
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(49 citation statements)
references
References 13 publications
3
12
1
4
Order By: Relevance
“…A similar impact of the education intervention was reported among Ghanaian women by a study that found that knowledge of cervical cancer and its screening test was significantly higher among women educated on cervical cancer than women without cervical cancer education (Ebu et al, 2019). The same findings were also reported by studies from Ethiopia and India (Abu et al, 2020;Thahirabanuibrahim & Logaraj, 2021).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…A similar impact of the education intervention was reported among Ghanaian women by a study that found that knowledge of cervical cancer and its screening test was significantly higher among women educated on cervical cancer than women without cervical cancer education (Ebu et al, 2019). The same findings were also reported by studies from Ethiopia and India (Abu et al, 2020;Thahirabanuibrahim & Logaraj, 2021).…”
Section: Discussionsupporting
confidence: 88%
“…This underlines the significant role of education in raising awareness that could help in early cervical cancer detection and prevention of late diagnosis and related complications, including deaths. This could encourage women to go for screening without waiting for symptoms since it was found that one of the reasons for not being screened early is the symptom absence (Abu et al, 2020). Therefore, this should be considered when establishing screening programs in Saudi Arabia, and appropriate measures should be taken to educate the population.…”
Section: Discussionmentioning
confidence: 99%
“…50 Our study revealed that in India efforts to promote screening under other existing health programs, via media or through the involvement of local NGOs is generally absent, although it would be an effective way to promote awareness about cervical cancer. 51 Collaborations with programs for school health, reproductive health, and family planning could also be envisaged to promote cervical cancer screening. The same applies to the broader education sector and local self-help groups, where village leaders can help to increase the credibility of the program.…”
Section: Discussionmentioning
confidence: 99%
“…Pemeriksaan dengan inspeksi visual dengan asam asetat (VIA) (Pinder et al, 2020), diikuti dengan pengobatan segera pada perempuan IVA-positif (pendekatan skrining dan pengobatan) dapat mengurangi jumlah kunjungan klinik dan secara signifikan meningkatkan kepatuhan pengobatan (Basu et al, 2018;Maza et al, 2017;WHO, 2013). Program skrining dengan IVA telah terbukti berhasil untuk mendiagnosis positif dan pengobatan lebih awal untuk lesi pra kanker (Abu et al, 2020;Wentzensen & Tamara, 2018). Oleh karena itu, implementasi IVA adalah intervensi yang menjanjikan yang akan membantu mengendalikan penyakit.…”
Section: Pembahasanunclassified